Oribatid mites (Acari: Oribatida) recorded from Ireland: Catalogue, historical records, species habitats and geographical distribution, combinations, variations and synonyms - Arroyo, Julio; Connell, Tagdh O; Bolger, Thomas (Zootaxa, 2017)
We provide a catalogue of the oribatid species (Arachnida, Acari, Oribatida) recorded from Ireland between the first records at the beginning of the 20th century and 2015. The catalogue, which contains 246 named species includes information on the habitats and locations where the species were found in Ireland as well as the references (if the data were published) where these were recorded. In addition, we include information on the species authorship, together with comprehensive nomenclatural data on synonyms and combination/variations of the named species. This catalogue increases the number of oribatids species known in Ireland by 50% since the most recent catalogue published in 1998 by Malcom Luxton.